Analisis Sistem Informasi Akuntansi Penggajian Dalam Mendukung Pengendalian Intern Pada PT Perkebunan Nusantara III (Persero) Kebun Bandar Selamat Kec. Aek Songsongan Kab. Asahan - Panjaitan, Latifah Hanum Br; Rahma, Tri Inda Fadhila; Harahap, Rahmat Daim (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This research aims to determine the payroll accounting information system in supporting internal control at the company PT Perkebunan Nusantara III (Persero) Kebun Bandar Selamat Kec. Aek Songsongan Kab. Asahan, whether the payroll accounting information system is in accordance with theory in its implementation and whether it supports internal control , as well as solutions to resolve problems that cause the payroll accounting information system to not support internal control. The data collection techniques used in this research were observation, interviews and documentation. The subjects in this research were 4 people who were employees at the company PT Perkebunan Nusantara III (Persero) Kebun Bandar Selamat District. Aek Songsongan District. Asahan is the Manager of the company PT. Perkebunan Nusantara III (Persero) Kebun Bandar Selamat District. Aek. Songsonan District. Asahan, Personnel section of the company PT Perkebunan Nusantara III (Persero) Kebun Bandar Selamat Kec. Aek Songsongan District. Asahan, Payroll Accounting section of the company PT. Perkebunan Nusantara III (Persero) Kebun Bandar Selamat District. Aek Songsongan District. Asahan, and the Finance section of the company PT Perkebunan Nusantara III (Persero) Kebun Bandar Selamat Kec. Aek. Songsonan District. Sharpening. This research uses a descriptive method with a qualitative approach. The results of this research show that the payroll accounting information system at the company PT Perkebunan Nusantara III (Persero) Kebun Bandar Selamat District. Aek Songsongan District. Asahan has used a computerized system but it has not supported internal control because it is not in accordance with theory, including the lack of functions used, documents used and accounting records used, and the lack of an adequate authorization system for implementing healthy practices in the elements contained in internal control.